Seismic shear demand of a medium-rise building designed by response spectrum analysis - Ky Leng (Chulalongkorn University, 2012)
According to ASCE7-05, response spectrum analysis (RSA) procedure can be used to determine the seismic demands of the structures for the seismic design of any type of structures. However, this design procedure has been found to be inappropriate for medium-rise and high-rise buildings. This paper is aimed at verifying the RSA procedure prescribed in the current Thai seismic design code which is based on ASCE7-05 and proposing an appropriate improvement to the RSA procedure if needed. A 16-story medium-rise reinforced-concrete core-wall case-study building is first designed based on RSA procedure and then the non-linear response history analysis (NLRHA) is performed to determine the more accurate seismic demands of the structure. The results show that seismic shear demand of the shear wall from non-linear analysis is about 2 times the shear capacity of the wall designed by RSA procedure. This could lead to shear failure in the shear walls designed by RSA procedure. This study used a modified RSA procedure proposed by Priestly and Amaris (2002) to calculate the design shear force in the walls. In this approach, the Reff (Effective response modification factor) more than 1 is used only for the first mode of translational (E-W direction) and torsional modes, and Reff = 1 is used for other higher modes. The results indicate that this new method could help avoid shear failure in the shear walls.